Measuring and understanding the world through geoinformatics using the example of natural hazards - Höfle, Bernhard (Measurement and understanding in science and humanities, 2023)
New digital data is being created at every moment in an unprecedented quantity, such as new web content, satellite images or photos taken with a smartphone. We learn about natural disasters via digital media, especially via websites with user-generated content and via “social media”, where information from the scene of the event can be shared by affected persons but also by emergency forces.